A multidisciplinary clinic approach to improve physician-related diagnostic delay for patients with axial spondyloarthritis: a retrospective study. Issue 6 (June 2019) - Li, Jiajie; Xu, Yuan; Chen, Yuling; Ye, Chunhua; Huang, Jiaxian; Qian, Liping; Xin, Weiwei; Li, Ting; Ye, Shuang
Objective: To assess the diagnostic delay (DD) and physician-related DD (pDD) in patients with axial spondyloarthritis (SpA) and the potential benefits of a multidisciplinary clinic (MDC) approach. Methods: A retrospective study was undertaken among patients with axial SpA, which aimed to analyse DD, pDD and their risk factors. The influence of pDD on disease outcomes was examined. The pDDs among consecutive SpA patients in an MDC cohort were compared with propensity score matched historical controls (1:1). Results: A total of 208 patients with axial SpA formed the historical control group and 49 patients with axial SpA formed the MDC cohort after introduction of the MDC. The median DD and pDD in the historical controls were 25.5 and 10.0 months, respectively. A cut-off of pDD > 4 months was associated with more active disease and functional impairment. An initial visit to a non-rheumatologist was the most significant risk factor for pDD. Following MDC introduction, the median pDD decreased from 13 months to 1 month after adjustments were made for confounders such as sex, education level, history of smoking, human leukocyte antigen-B27 status and SpA/ankylosing spondylitis classification criteria. Conclusion: The MDC was a promising approach that resulted in a reduced pDD among patients with axial SpA.